River Water Chemistry in Romania: An Overview - Cezara Voica; Olivian Marincas; Ioana Feher; Andreea Maria Iordache (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
A comprehensive overview of the surface water status of Romania has been done by evaluating five main river streams. In this context, waters sampled from five different locations of Romanian rivers were examined to study the chemical composition of macro elements, heavy metals, respectively rare earth elements (REEs). Analysis of variance (ANOVA) was applied to highlight the variation of representative variables among target rivers: Aries, Somes, Mures, Olt, and Prut. The association between analytical techniques, such as inductively coupled plasma mass spectrometry (ICP-MS) followed by supervised chemometric methods (linear discriminant analysis- LDA) proved to be a very useful association, able to highlight interesting information about data variation from these rivers. The ICP-MS analytical technique is suitable for analyzing microelements, toxic elements, and rare earth elements (REEs) at very low levels in surface river water samples. This approach, followed by interpretation and data preparation with chemometric methods, represents a step forward to a more comprehensive and realistic analytical data interpretation. The concentrations of most heavy metals in water were classified as average annual value ranges. Some trends of decreasing or, in other cases, increasing were observed for particular items, as follows: Olt River had the highest maximum values, followed by Prut River and Mures River. Somes River had the smallest inorganic loadings on the opposite side, with no maximum mean detected values. Determination of REEs in various environmental samples is essential because it can be used to create a sample fingerprint. Monitoring river water quality is an indispensable part of water management, where river water might serve as the sole water resource for different purposes.